Legal aspects of confiscation of corrupt objects or goods in the crime of money laundering - Noviantoro, Andika (Universitas Wiralodra, 2023)
The criminal acts of corruption in Indonesia are currently at a dangerous stage because they have penetrated the foundations of the nation's life. For this reason, eradicating corruption is a top priority in the criminal justice system. This can be seen in Article 25 of Law Number 31 of 1999 concerning amendments to Law Number 20 of 2001 concerning the Eradication of Corruption Crimes, which regulates